2007
DOI: 10.5326/0430099
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Diagnosis of Nongastrointestinal Foreign Bodies in Dogs

Abstract: Clinical data and computed tomography (CT) studies were reviewed for 13 dogs with confirmed nongastrointestinal foreign bodies. Locations of foreign bodies were the nasal cavity, thoracic wall, retropharyngeal region, and cerebellum. Types of foreign bodies included small plant components, blades of grass, wooden sticks, cloth fibers, and a needle. Foreign bodies in five dogs were not identified on CT, and secondary reactions resembled neoplastic or fungal disease. In eight dogs, foreign bodies were recognized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
48
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 34 publications
7
48
0
2
Order By: Relevance
“…Fifteen FBs were found at the time of first surgery, amongst which only seven were identified at CT. These findings are consistent with a previous study in which FBs were not detected by CT in 5 of 13 dogs in which an FB was found at surgery (Jones & Ober ). In some instances, the plant material itself cannot be detected at CT, and only the inflammatory response is seen.…”
Section: Discussionsupporting
confidence: 93%
“…Fifteen FBs were found at the time of first surgery, amongst which only seven were identified at CT. These findings are consistent with a previous study in which FBs were not detected by CT in 5 of 13 dogs in which an FB was found at surgery (Jones & Ober ). In some instances, the plant material itself cannot be detected at CT, and only the inflammatory response is seen.…”
Section: Discussionsupporting
confidence: 93%
“…The surrounding tissue inflammatory reaction may constitute the most visible abnormality, which is seen as hyperintense lesions relative to the surrounding musculature on T1-and T2-weighted MRI images and usually exhibits contrast enhancement, as described for foreign bodies in canine sublumbar musculature 5 . Computed tomography of non-gastrointestinal wooden foreign bodies has been described in dogs 10 . The CT identification of wooden foreign bodies in these cases was based primarily on linear shape or orientation along a plane that did not match a known anatomical structure 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography of non-gastrointestinal wooden foreign bodies has been described in dogs 10 . The CT identification of wooden foreign bodies in these cases was based primarily on linear shape or orientation along a plane that did not match a known anatomical structure 10 . In human cases, wooden sticks have been described to have an increased attenuation on CT images because of their high inherent density or absorption of fluids.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study of 13 non-gastrointestinal foreign bodies in dogs showed that 38 per cent of them could not be identified on CT scan (5/13) and 31 per cent of them had similar soft tissue opacity as neoplastic and inflammatory disorders (4/13). Conversely, foreign bodies with a particular shape or opacity were more likely to be distinguished with CT (Jones and Ober 2007). …”
Section: Discussionmentioning
confidence: 99%